Pengaruh Suhu dan Waktu Tempering Terhadap Kekerasan, Struktur Mikro, dan Laju Korosi Baja Tahan Karat Martensitik 13Cr3Mo3Ni [The Influence of Time and Temperature Tempering on Hardness, Microstructure and Corrosion Rate of 13Cr3Mo3Ni Stainless Steel] - Hadi Perdana; Moch Syaiful Anwar; Andinnie Juniarsih; Efendi Mabruri (National Research and Innovation Agency (BRIN), 2017)
The 13Cr3Mo3Ni martensitic stainless steel is the modified 410 type steel for steam turbine blade application. This paper reports the effect of tempering temperature and time on hardness, microstructure and corrosion rate of the modified steel. Microstructure observation was performed using optical microscopy and SEM-EDS, hardness testing using Rockwell C hardness tester and the corrosion test in 3.5% NaCl solution using Gamry G750 instrument. In general, the hardness of the steel decreased with increasing of tempering temperature. However, the hardness increased at the tempering temperature 500-650 °C showing secondary hardening, and the metal carbides with sub-micron in sizes were observed in the microstructure. Longer tempering time of 6 h resulted in decreased hardness without secondary hardening It can be reported also that the tempering temperature changed the potential, current and rate of corrosion of the13Cr3Mo3Ni steel. AbstrakBaja tahan karat 13Cr3Mo3Ni merupakan modifikasi dari baja tahan karat martensitik 410 untuk digunakan sebagai material sudu pada turbin uap. Tulisan ini memaparkan pengaruh suhu dan waktu tempering terhadap kekerasan, struktur mikro dan laju korosi baja tahan karat martensitik 13Cr3Mo3Ni. Pengujian yang dilakukan adalah pengamatan struktur mikro menggunakan mikroskop optik dan SEM-EDS, uji kekerasan dengan Rockwell C dan uji korosi di dalam larutan 3,5% NaCl dengan alat Gamry G750. Secara umum kekerasan baja menurun dengan naiknya suhu tempering, kecuali pada suhu 500-650 °C terjadi peningkatan kekerasan akibat adanya secondary hardening dan karbida logam berukuran sub-mikron teramati sebagai penyebabnya. Peningkatan waktu tempering menjadi 6 jam mengakibatkan penurunan kekerasan dan penghilangan efek secondary hardening. Perbedaan suhu tempering juga menghasilkan perbedaan potensial, arus serta laju korosi baja 13Cr3Mo3Ni.